Paediatric airway reconstruction: a preliminary study - Asha'ari, Zamzil Amin; Sheikh Ab. Hamid, Suzina (Malaysian Medical Associations, 2008)
To set the foundation for developing a centre for airway reconstruction, we performed a retrospective database review of patients operated at a tertiary-care university hospital. Over the past 3-year period from 2004 onwards, five paediatric cases of airway reconstruction procedures were performed. All cases had a two stages laryngotracheal reconstruction (TSLTR) for laryngotracheal stenosis (LTS). All patients were children below 15 years and the mean age was 9 years. Only one patient had a Grade IV Myer-Cotton1 stenosis, the rest all had Grade III stenosis. Three out of four of the Grade III stenosis patients were successfully decannulated within one year, the other one died of causes unrelated to LTS. The grade IV patient was still under follow up and surgery was done only recently. This paper highlights the complexity of managing LTS in the paediatric age group and recommends the use of LTR with rib graft as a choice for the management of LTS.